Beliefs about Multilingualism with Respect to Translanguaging: A Survey among Pre-Service EFL Teachers in Indonesia - Gede E. Putrawan; Mahpul; Tuntun Sinaga; Son K. Poh; Olga V. Dekhnich (National Research Mordova State University, 2022)
Introduction. Recently, multilingualism and translanguaging have received considerable attention and are always a topic of interest and public debate in language education. However, to our knowledge, studies on pre-service EFL teachers' beliefs about multilingualism with respect to translanguaging in the Indonesian context have not appeared in the literature. Therefore, to address this gap, this research investigated beliefs about multilingualism with respect to translanguaging, including language separation, language use/mixing, and language support, among pre-service EFL teachers in the Indonesian context. Materials and Methods. This study is quantitative in nature, adopting a survey research design. We collected data from 270 pre-service EFL teachers using an online Likert scale questionnaire that lacked any potentially sensitive questions. They were between the ages of 17 and 26, and were English teacher candidates majoring in English education at higher education institutions on the Indonesian islands of Sumatra, Java, Sulawesi, and Kalimantan. The collected data were analyzed using descriptive statistics, which included the percentages and frequency distributions of the participants' Likert scale responses. Results. The current study's findings corroborate previous research indicating that teachers believe multilingualism and collaborative use of languages are potential assets that can benefit their students' language learning. Discussion and Conclusion. Language separation in EFL classrooms appears to be a point of contention for the majority of pre-service EFL teachers surveyed, with a preference for and support for multilingualism and translanguaging over language separation in EFL classrooms. They agree on the importance of using or mixing other languages in their classes. On the one hand, they believe that it is critical to avoid other language support in classrooms; on the other hand, they believe that other language support can benefit students, offering a wave of optimism about future language education. Therefore, there is a need to gradually introduce and include pedagogical translanguaging to the existing curricula. The integration of new multilingual facts and the implementation of translanguaging pedagogies are part of a larger educational renewal. There is a need to intentionally create a multilingual space (translanguaging space) in EFL classrooms to fully utilise studentsʼ multilingual capabilities creatively and critically because today many teachers struggle to reconcile the disparities between monolingual educational policies and the realities of multilingual classrooms.